Melaspilea tucumana, a new gall-forming lichenicolous fungus from the tropical Andes in Bolivia. (7th August 2014) - FLAKUS, Adam; ETAYO, Javier; KUKWA, Martin
Abstract: The new obligately lichenicolous fungus, Melaspilea tucumana Flakus, Etayo & Kukwa, inhabiting thalli of saxicolous Pertusaria s. lat. is described from Tucumano-Boliviano vegetation in Bolivia. The species is characterized by the gall formation and superficial, lirelliform to branched, aggregated apothecioid ascomata with widely exposed discs. The ascomata of M. tucumana are initially perithecioid and immersed in the host thallus, but become superficial and apothecioid when mature, and thus resemble the genus Buelliella . This may suggest the placement of the new species in Dothideomycetes.